Attenuation of actinic prurigo eruptions with Polypodium leucotomos supplementation. Issue 1 (9th December 2021) - Stump, Madeliene; Dhinsa, Harpinder; Powers, Jennifer; Stone, Mary
Abstract: Actinic prurigo is a rare pruritic photodermatosis. We report the use of Polypodium leucotomos extract in an 11‐year‐old female patient with actinic prurigo, resulting in a significant attenuation of her disease without development of adverse effects to date. Polypodium leucotomos exerts a pleiotropic immunomodulatory and antioxidant effect by shifting the balance from pro‐ to an antiinflammatory cytokine environment. This counteracts the effects of UV‐induced cellular damage characteristic of photodermatoses.